Resolving the complex CES1 genomic locus with Cas9-directed targeted long-read sequencing - E. Lekka; A. Ambrodji; A. Nater; A. Ballah; U. Amstutz; A. Ramette; C. R. Largiadèr (npj Genomic Medicine, 2026)
Abstract Carboxylesterase 1 (CES1) is a major hepatic enzyme involved in the metabolism of many ester-containing drugs and endogenous lipids. However, genomic analysis of the CES1 locus is challenging due to highly homologous regions that confound short-read sequencing. To overcome these limitations, we applied an optimized, PCR-free Oxford Nanopore Cas9-directed targeted sequencing (nCATS) approach to enrich and sequence up to 76 kb spanning CES1 and CES1P1 or CES1A2 . Long-read sequencing of 23 human blood samples and the HepG2 cell line achieved an average on-target coverage of ~40× and a read N50 of ~61 kb, enabling haplotype-resolved detection of structural and small variants. We identified five previously unrecognized major CES1 haplotypes and showed that many variants reported in public databases likely result from short-read misalignment. We also uncovered long inverted repeats flanking a fragile site that may promote recurrent structural rearrangements. This study provides improved reference sequences and deeper insight into CES1 diversity, with important implications for future pharmacogenetic research, personalized treatment for CES1-metabolized medications, and understanding inter-individual susceptibility to CES1-associated diseases. Moreover, these findings can support research on regulatory mechanisms controlling CES1 expression and function. More broadly, this approach represents a promising strategy for closing gaps in genetic testing of many other complex regions, thereby providing a foundation for improved genotyping relevant to pharmacogenomics and precision medicine.